2019
DOI: 10.1002/rsa.20876
|View full text |Cite
|
Sign up to set email alerts
|

Squares of Hamiltonian cycles in 3‐uniform hypergraphs

Abstract: We show that every 3-uniform hypergraph H " pV, Eq with |V pHq| " n and minimum pair degree at least p4{5`op1qqn contains a squared Hamiltonian cycle.This may be regarded as a first step towards a hypergraph version of the Pósa-Seymour conjecture.2010 Mathematics Subject Classification. Primary: 05C65. Secondary: 05C45.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 13 publications
0
2
0
Order By: Relevance
“…With a slightly different but essentially equivalent notion of inseparability this was proved in 16 and in 1, but for the sake of completeness we provide the argument.…”
Section: Uniformly Dense and Inseparable Graphsmentioning
confidence: 94%
“…With a slightly different but essentially equivalent notion of inseparability this was proved in 16 and in 1, but for the sake of completeness we provide the argument.…”
Section: Uniformly Dense and Inseparable Graphsmentioning
confidence: 94%
“…For the existence of the rth$$ r\mathrm{th} $$ power of a tight Hamilton cycle in k$$ k $$‐graphs, not much is known in general. Bedenknecht and Reiher [6] showed that any 3‐graph on n$$ n $$ vertices with codegree at least false(4false/5+ofalse(1false)false)n$$ \left(4/5+o(1)\right)n $$ contains the square of a tight Hamilton cycle, which was extended in [42] to arbitrary k2$$ k\ge 2 $$ and arbitrary r2$$ r\ge 2 $$.…”
Section: Introductionmentioning
confidence: 99%